LYMPH NODE HYPERPLASIA IN A CONGENITALLY DEFORMED BULL INOCULATED AT BIRTH WITH BOVINE LYMPHOSARCOMA MATERIAL - HATZIOLOS, B. C. (Journal of the Hellenic Veterinary Medical Society, 1969)
NO ABSTRACT AVAILABLE